Philosophical Tools Of Lean Six Sigma In Service Sector: Implications For Organisational Learning - Ezra Tan, Yi Chyn (Universiti Sains Malaysia, 2022)
Due to the comprehensiveness and effectiveness of Lean Six Sigma (LSS), it has become one of the most popular methodologies in various industries over the past decades. However, many LSS practitioners only treat LSS as a mere toolbox instead of applying its philosophy. This paper aims to present the significance of LSS philosophy in service sector and discover its relationship with organisational learning through the development of LSS training modules. Although many researchers have proven that LSS contributes to organisational success in service sector, there is still a gap between understanding the benefits of LSS and practicing it in an organisation. Therefore, the relationship between the five LSS philosophical topics (Lean Leadership, Lean Management, Lean Culture, Change Management, and Employee Engagement) and the three key constructs of organisational learning (commitment, knowledge, and performance) were investigated. The five LSS philosophical topics were developed into modules for service sector using ADDIE model and implemented in an IT and software development company in Penang, Malaysia. The implementation of LSS trainings have brought fruitful results to the company in terms of performance improvement, effectiveness in knowledge sharing, and higher commitment. Besides, this paper also examines the impact of LSS on organisational learning by constructing questionnaires to collect data from the partner company and conduct statistical analysis using Analysis of Variance (ANOVA). The results confirmed the significant differences for all constructs and concluded that LSS has a strong positive impact on organisational learning. Nonetheless, more empirical evidence is required to generalise the applicability of the module as the modules were only implemented in one service sector. Besides, the paper only presents five philosophical tools. Further research on other themes can be done to expand the research topic.